2003
DOI: 10.1007/s00520-004-0606-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications of dose rounding of chemotherapy to the nearest vial size

Abstract: The judicious application of dose rounding of chemotherapy agents is possible without any negative clinical effect. It is feasible to dose round to the nearest vial for those cytotoxic agents that are available in multiple vial sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 11 publications
1
61
0
3
Order By: Relevance
“…Pharmacists, rather than clinicians, may be the predominant health professionals performing this dose adjustment. 31,32 While important and interesting results have been obtained, there were a number of limitations of our study. The first of these is the modest response rate of just under 60%.…”
Section: Discussionmentioning
confidence: 88%
“…Pharmacists, rather than clinicians, may be the predominant health professionals performing this dose adjustment. 31,32 While important and interesting results have been obtained, there were a number of limitations of our study. The first of these is the modest response rate of just under 60%.…”
Section: Discussionmentioning
confidence: 88%
“…In such a case one vial of 400 mg plus 3 vials of 100 mg or 7 vials of 100 mg will be used. Accordingly we will save one 100 mg vial [5][6][7]. Another study applied dose rounded to chemotherapy such as oxaliplatin which is used heavily in colorectal cancer protocols.…”
Section: Fda For Non-hodgkin's Lymphoma (Nhl)mentioning
confidence: 99%
“…Authors reported the results with significant cost saving [2][3][4][5][6][7]. The most common method of calculating the dose of anticancer drugs is body surface area (BSA); a function of a patient's height and weight in addition to per weight basis.…”
mentioning
confidence: 99%
“…As formulated, this double check required that an oncology pharmacist review an electronic version of the patient's prescription; make sure that the prescription given to the patient included the correctly calculated, clinically appropriate dose, which was in alignment with the previously published, internally approved chemotherapy regimens described earlier; and discuss and resolve dose discrepancies directly with the prescribing health care provider in a timely manner. A discrepancy between prescribed and intended dose of 10% or greater, a threshold based on clinical judgment and precedent, 3,4 was to prompt a telephone call and electronic message to the prescribing health care provider. In turn, the pharmacist was to provide medical record documentation that a double check had occurred with a description of outcome.…”
Section: Designing and Implementing The Safety Double Checkmentioning
confidence: 99%